CYRTODACTYLUS CONSOBRINUS (Peters’ Bent-toed Gecko) - Wen, Wong Jye; Chien, C. Lee; Izneil, Nashriq; Das, Indraneil (Society for the Study of Amphibians and Reptiles, 2021)
A field observation on attempted predation by the gekkonid, Cyrtodactylus consobrinus on spider eggs is made.